Empowering EFL teachers to craft dynamic English lessons that align with the Merdeka Curriculum - Nur Muthmainnah; Firmansyah Bayu Aji Manggala; Azza Musta’anudin (Nur Science Institute, 2026)
This program aimed to empower EFL teachers to design English lessons that align with the emancipated curriculum. Participatory action research was applied in this study which was conducted at an English teachers' community at junior high level (MGMP) in one of the regencies in Central Java, Indonesia.19 English teachers participated in this program. It covers planning, arrangement, development, and evaluation of the program. Planning was conducted through need analysis by employing a survey and FGD, it was found that classroom differentiation was the major challenge for English teachers in implementing the national curriculum. Thus, a Differentiated Instruction (DI) material for the EFL classroom was designed to be integrated into the program. The workshop materials was arranged by collaborating with an expert and the program developer. Program development was implemented through a one day workshop. A documentation was used to collect the data in the program development. After joining the workshop, one of the English teachers' representatives was interviewed and expressed a positive view of the program.